Penerapan Art Therapy Melukis Bebas pada Pasien Halusinasi Pendengaran - Nova Apriani; Novita Anggraini; Aprida Manurung (Lembaga Pengembangan Kinerja Dosen, 2026)
Hallucinations are false sensory perceptions unrelated to real external stimuli. Patients will have difficulty distinguishing whether the stimuli they experience originate internally (thoughts or feelings) or externally. This condition may affect any of the five senses. The most common type of hallucination is auditory hallucinations. One way to reduce the signs and symptoms of auditory hallucinations is through Art Therapy: freehand painting. To determine nursing care with the application of free painting therapy in patients with auditory hallucinations at the Mitra Mulia Husada Foundation, Palembang. The design used was a case study describing the cases of four patients with auditory hallucinations. Subjects were selected according to inclusion and exclusion criteria. The intervention provided was free-drawing therapy for four days, each lasting 30 minutes.After the intervention of applying free painting therapy for 4 days with a time of 30 minutes per visit, it was found that there was a decrease in signs and symptoms of hallucinations as shown through the results of the observation sheet in each patient. Mr. A. originally 9 became 3 signs of symptoms, Mr. S originally 7 became 3 signs of symptoms, Mr. AJ originally 9 became 3 signs of symptoms and Mr. M originally 10 became 5 signs of symptoms of auditory hallucinations. There was a decrease in auditory hallucination scores in each patient after being given Art Therapy: free painting. For future researchers, it is hoped that they can conduct research on the application of free painting therapy so that it can be carried out more frequently so that the therapy carried out is more effective in reducing the signs and symptoms of hallucinations and also add respondents so that the application of the therapy given is more effective in reducing the signs and symptoms experienced by patients.